Role of high-avidity binding of human neutrophil myeloperoxidase in the killing of Actinobacillus actinomycetemcomitans. - Miyasaki, K T (1987)
The binding of the neutrophil enzyme myeloperoxidase (MPO) to microbial surfaces is believed to be the first step in its microbicidal activity. The MPO-H2O2-Cl- system is responsible for most oxidative killing of Actinobacillus actinomycetemcomitans by human neutrophils. There appear to be three forms of MPO (MPO I, II, and III), all of which can kill this organism in the presence of H2O2 and chloride. In this study, we characterized the binding of native human neutrophil MPO to A. actinomycetemcomitans by an elution procedure dependent on the cationic detergent cetyltrimethylammonium bromide. Binding of native MPO was rapid and reached apparent equilibrium within 1 min. A proportion of binding under equilibrium conditions was saturable and highly avid, with a capacity of 4,500 sites per cell and a dissociation constant of 7.9 X 10(-10) M. At equal protein concentrations, more MPO III bound than MPO II, and more MPO II bound than MPO I. The high-avidity interaction was inhibitable with yeast mannan and with the serotype-defining mannan of A. actinomycetemcomitans. Binding was also partially reversible with yeast mannan. MPO bound to the high-avidity sites did not oxidize guaiacol but oxidized chloride, as detected by the chlorination of taurine. MPO bound to the high-avidity sites was incapable of killing A. actinomycetemcomitans alone in the presence of H2O2 and Cl-, but potentiated killing when sufficient additional MPO was provided. The killing of A. actinomycetemcomitans by the MPO-H2O2-Cl- system was inhibited by yeast mannan and a serotype-defining mannan of A. actinomycetemcomitans. We conclude that high-avidity binding of MPO to the surface of A. actinomycetemcomitans is a mannan-specific interaction and that MPO bound to the high-avidity sites is essential but not alone sufficient to kill A. actinomycetemcomitans.